2019
DOI: 10.1016/j.ajhg.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Variants Disturbing the Transactivation Capacity of POU3F3 Cause a Characteristic Neurodevelopmental Disorder

Abstract: POU3F3, also referred to as Brain-1, is a well-known transcription factor involved in the development of the central nervous system, but it has not previously been associated with a neurodevelopmental disorder. Here, we report the identification of 19 individuals with heterozygous POU3F3 disruptions, most of which are de novo variants. All individuals had developmental delays and/or intellectual disability and impairments in speech and language skills. Thirteen individuals had characteristic low-set, prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 28 publications
6
64
0
Order By: Relevance
“…Conservation alignment indicating that the POU‐S domain is highly conserved across different species. To date, three variants affecting the POU‐S have been reported, including the current study (red) and the previous study (blue) (* Snijders Blok et al, 2019). POU‐S (yellow): POU‐specific domain; POU‐H (turquoise): POU homeodomain [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Conservation alignment indicating that the POU‐S domain is highly conserved across different species. To date, three variants affecting the POU‐S have been reported, including the current study (red) and the previous study (blue) (* Snijders Blok et al, 2019). POU‐S (yellow): POU‐specific domain; POU‐H (turquoise): POU homeodomain [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionsupporting
confidence: 52%
“…POU3F3 has two known functional domain, POU‐Specific (POU‐S) and POU‐Homeodomain (POU‐H), and both required for the site‐specific binding to the different target genes (He et al, 1989; Li et al, 1993; Phillips et al, 2000). Recently, pathogenic POU3F3 variants have been associated with a neurodevelopmental disorder called Snijders Blok‐Fisher syndrome (SNIBFIS) (OMIM: #618604), which is characterized by intellectual disability (ID) and developmental delay (DD), speech problems, hypotonia, autism spectrum disorders, and overlapping dysmorphic features (Snijders Blok et al, 2019). In their report, 19 individuals with heterozygous POU3F3 variants have been reported: frameshift (9 of 19), missense (5 of 19), nonsense (4 of 19), and inframe deletion (1 of 19) type of variants constituted the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The two TF families with strongest enrichment and lowest p-values are POU domain genes (POU3F1/2/3, POU1F1, POU2F2) and GSX1/2 (S8B Fig). Both of them are involved in neurogenesis [54][55][56]. Motifs of SOX10, which is critical during embryonic development, are also enriched in low-LoF-tolerance enhancers [57][58][59].…”
Section: Lof-tolerance and Network Properties Of Enhancersmentioning
confidence: 99%
“…We identified recurrent variants within three fetal brain enhancer clusters associated with genes involved in nervous system development (CSMD1, OLFM1, POU3F3), and found that this enrichment was significant relative to expectations. All three genes show high pLI score (1, 1, 0.88 respectively), indicating that they are intolerant to loss of function variants and dosage sensitive, and one of them (POU3F3) was recently shown to harbor disease-causing heterozygous variants in patients with ID 52 . Our results suggest that enhancer variants could lead to dysregulation of these genes during nervous system development and thereby contribute to the etiology of ID.…”
Section: Discussionmentioning
confidence: 99%
“…All three genes (CSMD1, OLFM1 and POU3F3) play a role in nervous system development [48][49][50] . Heterozygous variants in POU3F3 protein coding regions have been recently implicated in ID 51,52 . A known role of these genes in nervous system development and the presence of recurrent variant in enhancer clusters associated with these genes in ID cohort suggest that these enhancer DNVs may contribute to ID.…”
Section: Recurrently Mutated Enhancer Clustersmentioning
confidence: 99%